A száműzött királyfi Habsburg Ottó alakjának szimbolikus és narratív megformálásai - Nagyillés Anikó; Blaskó Mária; „A királyhűség jól bevált útján...” Rendi és nemzeti kötődések szimbolikus változásai 1867 és 1918 között (2014) (Szeged) (2016)
In my essay I dissect a novel of Mária Blaskó, whose title is ”A Kiskirály” (the little king). My essay is a casework and it is an example, how could adapt the church the respect and loyalty for the Habsburg dynasty to catholic denominational. This loyality of catholic church for the king was significant after the WW1 too. I dissect the aims of royalists (”legitimists”) in the everyday life. The literary works of Blaskó connected with the ”Szívgárda” (Children’s Apostleship of Prayer) This association’s task was the religious childrearing and the pastoral activity. In the association was part of the devotion of the Sacred Heart of Jesus.The novel has two kind of interpretations. On the one hand is it a dynastic based revisionist intention. In this interpretation became King Charles IV., who was crowned with Holy Crown of Hungary the symbol of the integrity of the Hungarian crown and Crown Prince Otto meant the rightness and continuity of the legitimists demand. On the other hand refered this novel the religiosity, which was full of all aspects of life. It named enthronement of Jesus. The Aim of Szívgárda was the religious childrearing and the familie taken into the religious life and into the work of the church. This thought is perceptible in the book of Mária Blaskó. She regard Charles and his family as ideal family, who could set an example for the Hungarian families.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Nyelvek és irodalom